First meetings eaudiobook - Card, Orson Scott (Ender Wiggin, 2010)
Welcome to the Enderverse. When Orson Scott Card first published "Ender's Game" as a novella in 1977, few would have predicted that it would become one of the most successful ventures in publishing history. Expanded into a novel in 1985, Ender's Game won both the Hugo Award and the Nebula Award for Best Novel. Never out of print and translated into dozens of languages, it is the rare work of fiction that can truly be said to have transcended a genre. Ender's Game and its sequels have won dozens of prestigious awards and are as popular today among teens and young readers as adults. First Meetings is an audiobook collection of three novellas-plus the original " Ender's Game "-that journey into the origins and the destiny of one Ender Wiggin. " The Polish Boy " begins in the wake between the first two Bugger Wars when the Hegemony is desperate to recruit brilliant military commanders to repel the alien invasion. In John Paul Wiggin-the future father of Ender -they believe they may have found their man. Or boy. In " Teacher's Pest "-a novella written especially for this collection-a brilliant but insufferably arrogant John Paul Wiggin, now an American university student, matches wits with an equally brilliant graduate student named Theresa Brown. It is many years since the end of the Bugger Wars in " The Investment Counselor ." Ender's reputation as a hero and savior has suffered a horrible reversal. Banished from Earth and slandered as a mass murderer, twenty-year-old Andrew Wiggin wanders incognito from planet to planet as a fugitive. Until a blackmailing tax inspector compromises his identity and threatens to expose Ender the Xenocide. THE ENDER UNIVERSE Ender series Ender's Game / Speaker for the Dead / Xenocide / Children of the Mind / Ender in Exile / Children of the Fleet Ender's Shadow series Ender's Shadow / Shadow of the Hegemon / Shadow Puppets / Shadow of the Giant / Shadows in Flight The First Formic War (with Aaron Johnston) Earth Unaware / Earth Afire / Earth Awakens The Second Formic War (with Aaron Johnston) The Swarm / The Hive Ender novellas A War of Gifts / First Meetings